Positive solutions of integrodifferential equations. (1993) - Philos Philos, Ch. G. Ch. G.
Abstract : Integrodifferential equations of the forms x ′ ( t ) + p ( t ) ∫ 0 t K ( t − s ) x ( s ) d s = 0 and x ′ ( t ) + q ( t ) ∫ − ∞ t K ( t − s ) x ( s ) d s = 0 are considered, where K ∈ C ( [ 0, ∞ ), [ 0, ∞ ) ), p ∈ C ( [ 0, ∞ ), [ 0, ∞ ) ) and q ∈ C ( ( − ∞, ∞ ), [ 0, ∞ ) ) . Necessary conditions and also sufficient conditions for the existence of positive solutions are established.